Effect of process parameters on mechanical properties of mesta (Hibiscus cannabinus) adhesive-bonded nonwoven. Issue 1 (2nd January 2022) - Sengupta, Surajit; Ghosh, Papai; Mustafa, Izhar
Abstract: Mesta bonded nonwoven of 120 g/m 2 with poly-vinyl alcohol was made using impregnation-squeezing – drying-curing method. The effect of three process parameters adhesive concentration, squeezing pressure and curing temperature on the add-on and mechanical properties of the fabric, i.e. tenacity, breaking elongation, initial modulus, energy-to-break, stress relaxation, creep, bursting strength and tearing strength, have been studied using 20 points central composite rotatable design. All these properties have a significant effect on the performance of fabric in different uses. Second-order polynomials have been proposed with a good correlation for all these properties. From these models and contour diagrams, the effects of different parameters on mechanical properties have been discussed elaborately. Moreover, the models can also predict the properties satisfactorily knowing the values of factors or parameters. The predicted value show good agreement with observed values. The information available from these models and subsequent contour diagrams regarding the interactions of parameters on properties are very much useful to design a mesta adhesive-bonded nonwoven fabric. The critical point must be taken care of for designing a fabric for particular end use. To get the optimum mechanical properties of 120 g/m 2 fabric, the process parameters will be 20% adhesive concentration, 1.2 N/cm 2 squeezing pressure and 120 °C curing temperature with the same experimental setup and other parameters.